Case studies of existing human tissue repositories : "best practices" for a biospecimen resource for the genomic and proteomic era - Eiseman, Elisa (RAND, 2003)
Case studies of twelve existing human biospecimen repositories performed to evaluate their utility for genomics- and proteomics-based cancer research and to identify?best practices? in collection, processing, annotation, storage, privacy, ethical concerns, informed consent, business plans, operations, intellectual property rights, public relations, marketing, and education that would be useful in designing a national biospecimen network.
"MG-120."
Keywords: Tissue banks -- Case studies.; Preservation of organs, tissues, etc. -- Case studies.; Cadaver homografts -- Case studies.; Organizational Case Studies; Tissue Banks -- standards; Tissue Preservation -- methods; United States; Banques de tissus -- Études de cas.; Conservation des organes, tissus, etc. -- Études de cas.; MEDICAL -- Allied Health Services -- General.; MEDICAL -- Health Policy.; Tissue banks.; Preservation of organs, tissues, etc.; Cadaver homografts.; Tissue Banks -- standards -- United States.; Organizational Case Studies -- United States.; Tissue Preservation -- methods -- United States.; Cadaver homografts; Tissue banks; Case studies